ANALISA DAN PERANCANGAN SISTEM INFORMASI PERPAJAKAN PERHITUNGAN PAJAK PENGHASILAN (PPh 21) BAGI PESERTA KEGIATAN DI KECAMATAN CIMAHI UTARA - Resita Rahmadani; Aninda Safirah; Gunardi; Riky Faza (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The aim of this study is to analyze and design an accounting system of income-taxaccounting (PPh 21) for participants in activities in the northern city of Cimahidistrict. The design method used in the information system here uses the waterfallmethod. The gathering of information on this method is done by interviews,observation and library studies. From the observations made, there is a draglineaspect to the information processing process, and it still employs a manual systemin data users that uses only Microsoft Excel which is still less effective and efficientand requires a relatively long time in the income-tax counting process (PPh 21) forparticipants. Thus, it requires designing an income-tax accounting system (PPh 21)implemented using Microsoft Visual 2010 and Microsoft access 2013. As the resultof this new system of things, it is expected to make Cimahi’s northern city easier todeduct Cimahi in the more optimum process of the income-tax counting process(PPh 21).